The Meaning of Destiny and Work Ethic in the Lyrics “Manusia Kuat” by Tulus - Annisa Silvia; Azka Rayyan Kamil; Julia Sukma; Muhammad Yurid Husna; Dadan Firdaus (INDO PUBLISHING, 2026)
This study aims to analyze the meanings of destiny and work ethic represented in the lyrics of Manusia Kuat by Tulus. The study employs a qualitative descriptive method using Geoffrey Leech’s semantic theory as the primary analytical framework. The data source consists of words, phrases, and sentences found in the song lyrics that reflect the concepts of destiny and work ethic. Data were collected through documentation and note-taking techniques and analyzed using an interpretative semantic approach. The findings reveal that the lyrics contain various semantic meanings, particularly affective, connotative, thematic, and reflective meanings. The concept of work ethic is represented through expressions of perseverance, resilience, optimism, determination, and commitment to achieving personal goals. Meanwhile, the concept of destiny is reflected in expressions that emphasize acceptance of circumstances beyond human control and recognition of divine will. Furthermore, the study shows that destiny and work ethic are closely interconnected in the song. The lyrics suggest that accepting destiny should not lead to passivity but should encourage individuals to continue striving despite obstacles and uncertainties. Therefore, Manusia Kuat conveys a balanced life message that combines acceptance of destiny with continuous effort and perseverance.